Activated carbon air filter and rubber seed oil approach from waste rubber seed shell for alternative fuel and improving air quality - Dafit Feriyanto; Supaat Zakaria; Alfian Noviyanto; Nurato Nurato; Dedik Romahadi; Hadi Pranoto; Samir Sani Abdulmalik (Universitas Mercu Buana, 2026)
Research related to rubber seed conversion to oil and activated carbon as filter media requires further exploration. Therefore, the main objective of this study to investigate the rubber seed oil as alternative energy and rubber seed Shell Activated Carbon (RSSAC). Thermo-chemical method conducted with separation process between the kernel and the shell. The process used temperatures of 550 and 600°C. Biodiesel was produced by a blending process using a frequency of 20kHz, temperature of 60oC and 2h holding time. In addition, the side product was converted into activated carbon through carbonization and activation using KOH. Air filter fabricated using three layers, where the top and bottom layers being non-woven and RSSAC in the middle. It compacted using hot-press method at temperature of 150°C for 60 s to produce an air filter media thickness of 3–5mm. The results show that there are several high compound concentrations i.e. CH4, aldehydes, and ketonestone. Several gases evolve, such as CO2, CO, CH4, H2O, ketone aldehyde, and HC. Microstructure analysis using Scanning Electron Microscope (SEM) of RSSAC shows that element C significantly increase up to 80%, while O, K, and Ca decreased up to 72%, 66% and 90%, respectively. RSSAC has a large surface area of 175.95m2/g, and it will have high effectiveness in improving indoor air quality (IAQ). This is indicated by the result of IAQ analysis where the humidity, temperature, CO, CO2, TVOC, and PM10 were lower than the acceptable limit of 70%, 27oC, 1000ppm, 10ppm, 3 ppm, and 0.15 mg/m3, respectively.